Analisis Persepsi Harga Terhadap Keputusan Pembelian Produk Xiaomi dan Samsung Dikalangan Mahasiswa - Wahyudi Prasetyo H; Hadi Muhamad R; Syamsul Hidayat (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research is a survey research on students who use Xiaomi and Samsung cell phones. The aim of this research is to determine and analyze the influence of price perceptions on purchasing decisions. The company's success in influencing consumer purchasing decisions is done by building good communication with consumers, building good product brands and providing new innovations in products produced by following current trends. This research aims to determine and analyze the influence of price and brand image on purchasing decisions. The data collection technique used in this research was based on a questionnaire with a sample size of 50 respondents. The analytical method used is multiple linear regression analysis. Based on the research results, the results of the simultaneous influence significance test with the F test, price and brand image together or simultaneously, have a significant (statistically) influence on purchasing decisions. Based on the results of the partial influence test with the t test, it is known that the independent variables, namely the lifestyle variable have a negative effect and do not have a significant effect on purchasing decisions, price has a positive but not significant effect on purchasing decisions, and brand image has a positive and significant effect on purchasing decisions. . Suggestions for Xiaomi and Samsung companies are that they should look at the lifestyle needs of consumers, don't just focus on the product, set prices according to market share in smartphone product sales, and carry out promotions that are right on target with good concepts and designs.